Engineering better biofilms for environmental and chemical application - Low, Desmond Jia Jun (2015)
This study investigates the removal capabilities of the planktonic and biofilm cultures of Comamonas Testosteroni WDL7/Wild Type (WT) and Comamonas Testosteroni WDL7/pYedQ2 on steroidal hormones E1, E2, EE2 and testosterone. The WDL7/pYedQ2 mutant strain have increased levels of second messenger c-di-GMP which enhances biofilm formation and have been proven capable of improving biofilm-based biodegradation (Wu et al., 2014). The planktonic cultures of both strains showed insignificant removal of the steroidal hormones. Instead, it was the syringe filter that was used to filter the samples, which had removed the E1, E2, EE2 and testosterone contents along with the bacteria cells. The estrogens were easily adsorbed onto the syringe filters as compared to testosterone. In contrast to the planktonic cultures which showed insignificant removal, the biofilm cultures of WDL7/WT and WDL7/pYedQ2 demonstrated significant removal of the steroidal hormones. By day 3, the removal rates of the steroidal hormones were approximately 98% for testosterone, followed by E2 at 91%, E1 at 87% and EE2 at 84%.